Determination of the anticoagulant effects of new oral anticoagulants: an unmet need - Harenberg, Job; Hetjens, Svetlana; Erdle, Sandra; Krämer, Roland (Expert review of hematology, 2014)
Thromboembolic diseases require anticoagulation for their prevention and treatment. New oral anticoagulants, specifically direct factor Xa and thrombin inhibitors, were developed to overcome the limitations of conventional anticoagulants. Their benefit has been demonstrated using fixed doses without laboratory-guided dose adjustment for patients following elective knee and hip replacement, treatment of venous thromboembolism and prevention of embolic events in atrial fibrillation. These anticoagulants are excreted by glomerular filtration at a rate of between 25 and 80%. Thus, lower doses are required for patients with impaired renal function. Therefore, determination of the anticoagulant effects may be needed in other specific patient populations. Prothrombin time, activated partial thromboplastin time, prothrombin-induced clotting time, ecarin clotting time, hemoclot assay, other specific coagulation assays and chromogenic substrate are available to determine the effect of the anticoagulants. Standardization of methods, development of point-of-care tests and identification of patient groups is ongoing.